PENGELOLAAN PENDAPATAN ASLI DAERAH MELALUI OPSEN PAJAK KENDARAAN BERMOTOR BERDASARKAN UNDANG - UNDANG NOMOR 1 TAHUN 2022 DI PROVINSI SUMATERA UTARA - Azis Salim; Mirza Nasution; EKA N.A.M. Sihombing (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: Locally-Generated Revenue (PAD) serves as a crucial indicator for measuring regional fiscal independence. In North Sumatra Province, the Motor Vehicle Tax (PKB) is a primary source of PAD, contributing dominantly to regional tax receipts. Following the enactment of Law Number 1 of 2022 concerning Financial Relations between the Central Government and Regional Governments (UU HKPD), a PKB *opsen* (additional tax levy/surcharge) policy was introduced to replace the Revenue-Sharing Fund (DBH) scheme, aiming to enhance the effectiveness of regional revenue collection and strengthen the fiscal independence of regency and city governments. This study aims to analyze PAD management through the PKB *opsen* in North Sumatra Province, examine the pre-existing PKB revenue-sharing allocation procedures, and project the impact of the PKB *opsen* policy implementation on regional revenue. The study employs a socio-legal (empirical-juridical) method, utilizing both statutory and field-based approaches. Data were gathered through literature reviews, analysis of laws and official government documents, and interviews with stakeholders involved in regional tax management in North Sumatra Province. The findings indicate that the previous PKB revenue-sharing scheme faced various obstacles, particularly delays in fund disbursement to regency and city governments caused by lengthy bureaucratic procedures. Implementing the PKB *opsen* has the potential to improve the efficiency of tax revenue distribution through direct disbursement mechanisms into regency/city treasuries, thereby accelerating PAD receipt and bolstering regional fiscal independence. Conversely, potential challenges exist, such as uncertain public perception regarding the tax burden and a possible decline in gross revenue at the provincial level. Therefore, the successful implementation of the PKB *opsen* requires synergy among the provincial government, regency/city governments, the police, and relevant agencies to enhance taxpayer compliance and optimize regional tax revenue management. Keywords: Locally-Generated Revenue, Motor Vehicle Tax, Tax *Opsen* (Additional Levy), Revenue-Sharing Fund, Fiscal Independence, North Sumatra Province.   Abstrak: Pendapatan Asli Daerah (PAD) merupakan indikator penting dalam mengukur kemandirian fiskal daerah. Di Provinsi Sumatera Utara, Pajak Kendaraan Bermotor (PKB) menjadi salah satu sumber utama PAD dengan kontribusi yang dominan terhadap penerimaan pajak daerah. Seiring berlakunya Undang-Undang Nomor 1 Tahun 2022 tentang Hubungan Keuangan antara Pemerintah Pusat dan Pemerintahan Daerah (UU HKPD), diperkenalkan kebijakan opsen PKB sebagai pengganti skema Dana Bagi Hasil (DBH) guna meningkatkan efektivitas penerimaan daerah dan memperkuat kemandirian fiskal pemerintah kabupaten/kota. Penelitian ini bertujuan untuk menganalisis pengelolaan PAD melalui opsen PKB di Provinsi Sumatera Utara, mengkaji prosedur alokasi DBH PKB sebelum berlakunya opsen, serta memproyeksikan dampak implementasi kebijakan opsen PKB terhadap penerimaan daerah. Penelitian ini menggunakan metode yuridis empiris dengan pendekatan perundang-undangan dan pendekatan lapangan. Data diperoleh melalui studi kepustakaan, analisis peraturan perundang-undangan, dokumen resmi pemerintah, serta wawancara dengan pihak terkait dalam pengelolaan pajak daerah di Provinsi Sumatera Utara. Hasil penelitian menunjukkan bahwa skema DBH PKB yang berlaku sebelumnya masih menghadapi berbagai kendala, terutama keterlambatan penyaluran dana kepada pemerintah kabupaten/kota akibat prosedur birokrasi yang panjang. Penerapan opsen PKB berpotensi meningkatkan efisiensi distribusi penerimaan pajak melalui mekanisme penyaluran langsung ke kas daerah kabupaten/kota, sehingga mempercepat penerimaan PAD dan memperkuat kemandirian fiskal daerah. Di sisi lain, terdapat potensi tantangan berupa ketidakpastian persepsi masyarakat terhadap beban pajak serta kemungkinan penurunan penerimaan bruto di tingkat provinsi. Oleh karena itu, keberhasilan implementasi opsen PKB memerlukan sinergi antara pemerintah provinsi, pemerintah kabupaten/kota, kepolisian, dan instansi terkait untuk meningkatkan kepatuhan wajib pajak serta mengoptimalkan pengelolaan penerimaan pajak daerah. Kata Kunci: Pendapatan Asli Daerah, Pajak Kendaraan Bermotor, Opsen Pajak, Dana Bagi Hasil, Kemandirian Fiskal, Provinsi Sumatera Utara.